Digital transformation of the economy and business - Aubakirova, D.A. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2022)
Starting as digitalization, the process of introducing digital technologies in various sectors of the economy has taken on a comprehensive scale. The "race of technological reequipment" has already begun, and its main content is the digital transformation of business [1]. Platform solutions and networking principles of doing business are spreading. It both works and brings benefits to companies, radically transforming business processes, and forming entire ecosystems. World experts agree that only digital technologies in the coming years will be a driver of economic development in almost all spheres of human life, and the volume of the digital economy by 2023 will be 23 trillion dollars. Integration of technologies into the real world has led to the fact that they are so tightly integrated into the processes of production, doing business, training and public administration that further growth is impossible to imagine without "digital". And amid the COVID-19 pandemic, the rapid digital transformation of entire industries has become not just a necessity, but a measure to survive. Today we need to talk not about the digital transformation of the traditional economy, but about the formation of a new exponentially accelerating economy, the existence of which is impossible without digital technologies, a digital society and a system of global relations.
Keywords: Digital economy; transformation; digital technologies; state; economy; innovations